The role of low angle grain boundary in deformation of titanium and its size effect. (1st April 2019) - Chen, Sijing; Yu, Qian
Abstract: By performing in situ transmission electron microscope (TEM) experiments and three dimensional dislocation tomography, we report the effect of low angle grain boundary (LAGB) on deformation of a titanium material and its size effect. It is found that at large scale the LAGB can either act as dislocation nucleation site or as "tunable" barrier that allows selective transmission of dislocations. As the physical dimension of the sample decreases to submicron scale, LAGB was found to strongly hinder dislocation motion but dissipate energy through migration under high stress, similar to the behavior of high angle grain boundaries at large scale. Graphical abstract: Unlabelled Image